The Business of OPEN SOURCE. - Watson, Richard T.; Boudreau, Marie-Claude; York, Paul T.; Greiner, Martina E.; Wynn Jr., Donald (Communications of the ACM, 2008)
The article focuses on the open source software (OSS) industry. It mentions that there is an abundance of new and innovative products emerging from the OSS community because of the zero-licensing structure of most open source projects. After enumerating the five models underlying the software development business including proprietary, open community, corporate distribution, sponsored OSS and second-generation OSS (OSSg2), the author declares that OSSg2 firms control the software code unlike other firms, have effective strategies and offer a significant customer value proposition. The author asserts that OSSg2 firms have a very promising business model that could emerge as a dominant model in the coming years.